2022
DOI: 10.3389/fmed.2022.852187
|View full text |Cite
|
Sign up to set email alerts
|

How Healthcare Utilization Due to Dizziness and Vertigo Differs Between Older and Younger Adults

Abstract: BackgroundVertigo and dizziness are common in older adults. We describe self-reported healthcare utilization because of dizziness and vertigo in older adults attending a tertiary care specialized vertigo center.MethodsData from 765 patients (45% were ≥60 years old) with chronic dizziness and vertigo who attended a daycare multimodal treatment program were recorded. Data included sociodemographic parameters, dizziness-related characteristics, the Body Sensations Questionnaire (BSQ), the Agoraphobic Cognitions Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…This could be demonstrated in the elastic net model after correction for cofactors and in the flexplot ( Figure 4 ). This effect occurred independent from the intensity of dizziness/vertigo, although it is known that dizziness-associated handicap increases with age ( 25 ) and older patients with dizziness have less anxiety than younger patients ( 26 ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This could be demonstrated in the elastic net model after correction for cofactors and in the flexplot ( Figure 4 ). This effect occurred independent from the intensity of dizziness/vertigo, although it is known that dizziness-associated handicap increases with age ( 25 ) and older patients with dizziness have less anxiety than younger patients ( 26 ).…”
Section: Discussionmentioning
confidence: 86%
“…In an earlier study, we found that younger people were more frequently hospitalized due to dizziness than older adults, and the number of consultations of healthcare providers was considerably higher in younger patients ( 26 ). Now, we can hypothesize that a higher tolerance of dizziness increases the threshold to initiate specialized vertigo therapy and could partly explain lower healthcare utilization in older patients.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…1). These results seem plausible because of the increased vestibulocochlear dysfunction with age [59][60][61][62], including the frequent cases without the patient noticing the vestibular dysfunction occurred [63][64][65]. Contrary, two published studies by Inui et al [40,58] showed that participants < 60 years had significantly larger TFS and ELS/TFS volume ratios in the inner ear and significantly larger ELS/TFS volume ratios in the vestibulum in comparison to the participant group ≥ 60 years.…”
Section: Els Age-dependencymentioning
confidence: 99%
“…Die Häufigkeit von Physiotherapieverordnungen bei Patient*innen mit S/G nimmt mit dem Alter der Patient*innen ab [18]. Sie schwankt zwischen 41,3 % bei jüngeren Patient*innen (Mittelwert (MW): 55,3 Jahre) [19] und 4,4 % bei über 65-Jährigen [20].…”
Section: Introductionunclassified